Early to Late Holocene Surface Exposure Ages From Two Marine‐Terminating Outlet Glaciers in Northwest Greenland. Issue 14 (29th July 2018) - Reusche, Melissa M.; Marcott, Shaun A.; Ceperley, Elizabeth G.; Barth, Aaron M.; Brook, Edward J.; Mix, Alan C.; Caffee, Marc W.
Abstract: Terrestrial chronologies from southern Greenland provide a detailed deglacial history of the Greenland Ice Sheet (GIS). The northern GIS margin history, however, is less established. Here we present surface exposure ages from moraines associated with two large outlet glaciers, Petermann and Humboldt, in the northwestern sector of the GIS. These moraine chronologies indicate a Little Ice Age advance of the ice sheet margin before 0.3 ka and a possible equivalent advance of similar magnitude prior to 2.8 ka. An early Holocene moraine at Humboldt Glacier was abandoned by 8.3 ± 1.7 ka and is contemporaneous with other moraines deposited along the entire western GIS margin. This widespread ice margin stability between 9 and 8 ka indicates that while this margin was influenced by warming atmospheric temperatures during the early Holocene, the warming was likely overprinted with the effect of the abrupt climate cooling at 9.3 and 8.2 ka. Plain Language Summary: The global climate is warming, and the Greenland Ice Sheet is responding. A more complete understanding of this process is needed to better predict its future response to climate change. We determine how the ice sheet changed following the last ice age in northwest Greenland. The northwest sector of the ice sheet retreated to the coast by 10, 000 years ago during a period of warming atmospheric temperatures. About 8, 300 years ago the ice stopped retreating despite relatively high atmospheric temperatures. A similar standstill occurred in areas along western Greenland between 9, 000 and 8, 000 years ago. This suggests that despite the long‐term warming, well‐known abrupt cooling events that occurred in the region at this time influenced the ice sheet margin and temporarily stopped the long‐term pattern of ice retreat. The ice sheet retreated after 8, 300 years ago and then advanced during the latest cold period, the Little Ice Age (1350–1850 CE), in a fashion similar to elsewhere in Greenland. Our study finds that the Greenland Ice Sheet margins are sensitive to both long‐term (>1, 000 years) and short‐term (<100 years) atmospheric temperature changes. This sensitivity of the ice margin has important implications when assessing ongoing and future ice loss today. Key Points: Both Early Holocene and Little Ice Age moraines are present in northwest Greenland Humboldt Glacier moraines were deposited during a period of ice margin stability along western Greenland around 8.3 ka The western GIS margin was sensitive to subcentennial‐scale atmospheric temperature fluctuations during the early Holocene